Technology-Based Learning Media for EFL Class in Elementary School in Taiwan - Budiman, Muhammad Arief; Tsai, Mei Chuan; Wu, Ting Ting (The Proceedings of English Language Teaching, Literature, and Translation (ELTLT), 2025)
Traditional learning media such as textbooks and flashcards are still widely used in EFL classrooms in Taiwanese elementary schools, but they often fail to engage digital-native students. This research aims to describe the use and challenges of digital-based learning media, including games, songs, and videos, in enhancing student engagement in EFL learning. The study uses a descriptive qualitative approach to explore the effectiveness of these media. Data were collected through questionnaires distributed to elementary school teachers in Taiwan. The results show that while digital-based media offer more interactive and engaging learning experiences, issues such as accessibility, technical difficulties, and student boredom still persist. The study concludes that integrating game-based, song-based, and video-based media can address these challenges and significantly improve student participation and learning outcomes in EFL classrooms.